Public knowledge and attitude toward vitiligo in Saudi Arabia: A cross-sectional study - Malak A M Algarni; Waleed A Alqarni; Logain G Alghanemi; Maryam M Alnashri; Rand G Alghanemi; Nouf T Mleeh (Wolters Kluwer Medknow Publications, 2021)
Background: Knowledge and positive attitude toward vitiligo would foster support for affected individuals, improving their sense of well-being and possibly treatment outcome. Purpose: To evaluate the levels of public knowledge and attitude toward vitiligo among Saudis. Methods: A cross-sectional study among 12,181 participants. Data were collected using a self-administered questionnaire enquiring about knowledge, attitude, and perceptions in vitiligo. Results: The response rate was 95.4%. Most respondents had heard about vitiligo (96.9%). The median knowledge score was four out of eight and median attitude score was six out of eight. Social media/Internet was the most commonly reported source of information (34.7%), followed by family/friends/acquaintances (30%). Higher proportions of correct responses were recorded regarding the noninfectious nature of vitiligo (85.0%) and whether vitiligo was dangerous or connected to skin cancer (63.4%). However, unsatisfactory responses were found regarding the immunological basis of the condition: only 24.3% knew that vitiligo was an immune disease and 24.5% knew about the role of heredity in vitiligo. The majority of respondents did not mind employing patients with vitiligo (89.0%). Only 40.6% responded that they would marry someone with vitiligo. Positive attitude was significantly common in respondents aged 31-50 years (P < 0.01), women (P < 0.01), and those who had a university degree or higher (P < 0.05). Conclusion: Although overall attitude toward vitiligo patients was positive, there were gaps in the knowledge, particularly regarding the nature of the disease. More awareness and education are required to improve attitude toward vitiligo patients, with an aim to improve their overall well-being.